The effects of axotomy on the conduction of action potentials in peripheral sensory and motor nerve fibres. - Milner, T E (1981)
Medial gastrocnemius and sural nerves in one hindlimb of the cat were transected and prevented from regenerating. After periods ranging from 29-273 days, compound action potentials were recorded from axotomised and contralateral control nerves. The amplitude and integrated area of action potentials decreased and conduction velocity slowed following axotomy. The area under compound action potentials generated by stimulating sensory fibres declined significantly faster than that generated by stimulating motor fibres. Analysis of changes in whole nerve conduction velocity distributions showed that the velocities of fast conducting sensory fibres decreased at the most rapid rate. The conduction velocities of motor fibres and slow sensory fibres declined at significantly slower rates. The loss of electrical activity in the largest sensory nerve fibres following axotomy, may play a role in determining the faster rate at which their action potentials deteriorate.